Penerapan Konseling Person Centered untuk Meningkatkan Motivasi Belajar Peserta Didik di SMP Negeri 4 Pa’jukukang (Universitas Negeri Makassar, 2021)
Application of Person Centered Counseling to Improve Students' Learning Motivation. This article is based on the author's observations and experiences, that in SMP Negeri 4 Pa'jukukang there are still many students who have low learning motivation. The purpose of this study was to determine the application of person centered counseling in increasing students' learning motivation at SMPN 4 Pa'jukukang for the Academic Year 2021/2022. This research method is descriptive qualitative. The research subjects were 6 students who had low learning motivation. Data collection techniques using observation or direct observation and interviews. The results showed that person centered counseling can increase students' learning motivation.